2014
DOI: 10.1016/j.conbuildmat.2014.08.070
|View full text |Cite
|
Sign up to set email alerts
|

Macro/micro-pore structure characteristics and the chloride penetration of self-compacting concrete incorporating different types of filler and mineral admixture

Abstract: The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk 1 Macro/Micro-pore structure characteristics and the chloride penetration of self- might be, primarily, responsible in determining the chloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…As observed in water absorption results, this performance may be attributed to the more packed microstructure and pore structure of the concrete by addition of fly ash. At the nano scale, the results demonstrated that the chloride penetration velocities were more closely related to the change in the CPDs in the cement matrix than to the APDs, including the capillary pores, in both the ITZ and the cement matrix as detected by the MIP [41].…”
Section: Capillary Water Absorptionmentioning
confidence: 89%
See 4 more Smart Citations
“…As observed in water absorption results, this performance may be attributed to the more packed microstructure and pore structure of the concrete by addition of fly ash. At the nano scale, the results demonstrated that the chloride penetration velocities were more closely related to the change in the CPDs in the cement matrix than to the APDs, including the capillary pores, in both the ITZ and the cement matrix as detected by the MIP [41].…”
Section: Capillary Water Absorptionmentioning
confidence: 89%
“…Furthermore, the charges passed of FA concrete were higher than that of SF concrete [44]. Another study demonstrates that the use of lime stone (LP) at relatively high replacement of cement increased the chloride penetration velocity of LP-SCC as compared with both the use of cement only (without any replacement) and the incorporating of mineral admixture such as FA and FA + SF at the same replacement percentage [41]. Results of water absorption and catalyzed chloride ion penetration tests show that nanosilica has a great influence on the reduction of water absorption and chloride ion penetration into fiber-reinforced concrete [49].…”
Section: Chloride Ion Penetrationmentioning
confidence: 95%
See 3 more Smart Citations